Smoking Affects Response to Inhaled Corticosteroids or Leukotriene Receptor Antagonists in Asthma - Lazarus, Stephen C. (American Thoracic Society, 2007)
Rationale: One-quarter to one-third of individuals with asthma smoke, which may affect response to therapy and contribute to poor asthma control. Objectives: To determine if the response to an inhaled corticosteroid or a leukotriene receptor antagonist is attenuated in individuals with asthma who smoke. Methods: In a multicenter, placebo-controlled, double-blind, double-dummy, crossover trial, 44 nonsmokers and 39 light smokers with mild asthma were assigned randomly to treatment twice daily with inhaled beclomethasone and once daily with oral montelukast. Measurements and Main Results: Primary outcome was change in prebronchodilator FEV(1) in smokers versus nonsmokers. Secondary outcomes included peak flow, PC(20) methacholine, symptoms, quality of life, and markers of airway inflammation. Despite similar FEV(1), bronchodilator response, and sensitivity to methacholine at baseline, subjects with asthma who smoked had significantly more symptoms, worse quality of life, and lower daily peak flow than nonsmokers. Adherence to therapy did not differ significantly between smokers and nonsmokers, or between treatment arms. Beclomethasone significantly reduced sputum eosinophils and eosinophil cationic protein (ECP) in both smokers and nonsmokers, but increased FEV(1) (170 ml, p = 0.0003) only in nonsmokers. Montelukast significantly increased a.m. peak flow in smokers (12.6 L/min, p = 0.002), but not in nonsmokers. Conclusions: In subjects with mild asthma who smoke, the response to inhaled corticosteroids is attenuated, suggesting that adjustments to standard therapy may be required to attain asthma control. The greater improvement seen in some outcomes in smokers treated with montelukast suggests that leukotrienes may be important in this setting. Larger prospective studies are required to determine whether leukotriene modifiers can be recommended for managing asthma in patients who smoke.